Multiplex PCR for Species-Level Identification of Bacillus anthracis and Detection of pXO1, pXO2, and Related Plasmids - Riojas, Marco A. (Health Secur, 2015)
The Bacillus anthracis virulence plasmids pXO1 and pXO2 have critical implications for biosafety and select agent status. The proper identification and characterization of B. anthracis and its plasmid profile is important to the biodefense research community. Multiplex PCR was used to simultaneously detect a B. anthracis–specific chromosomal mutation, 4 targets distributed across pXO1, 3 targets distributed across pXO2, and highly conserved regions of the 16S gene, allowing an internal positive control for each sample. The multiplex PCR can produce as many as 9 easily separable and distinguishable amplicons, ranging in size from 188 to 555 bp. The PCR results were used to characterize DNA samples extracted from B. anthracis, other Bacillus species, and other bacterial species from many different genera. With the exception of 2 novel putative plasmids discovered, testing against inclusion and extensive exclusion panels showed 100% correlation to previously published and expected results. Upon testing 29 previously unpublished B. anthracis strains, 10 (34.5%) were pXO1(+)/pXO2(+), 9 (31.0%) were pXO1(+)/pXO2(−), 7 (24.1%) were pXO1(−)/pXO2(+), and 3 (10.3%) were pXO1(−)/pXO2(−). The present work presents a novel 9-target multiplex PCR assay capable of species-level identification of B. anthracis via a unique chromosomal marker and the detection of pXO1 and pXO2 via multiply redundant targets on each.